2005
DOI: 10.1016/j.devcel.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Wnt9b Plays a Central Role in the Regulation of Mesenchymal to Epithelial Transitions Underlying Organogenesis of the Mammalian Urogenital System

Abstract: The vertebrate urogenital system forms due to inductive interactions between the Wolffian duct, its derivative the ureteric bud, and their adjacent mesenchymes. These establish epithelial primordia within the mesonephric (embryonic) and metanephric (adult) kidneys and the Müllerian duct, the anlage of much of the female reproductive tract. We show that Wnt9b is expressed in the inductive epithelia and is essential for the development of mesonephric and metanephric tubules and caudal extension of the Müllerian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
774
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 801 publications
(803 citation statements)
references
References 39 publications
22
774
3
4
Order By: Relevance
“…Wnt7b is weakly expressed in the Wolffian duct and the stalk of the UB but not in the vertical portion or tips of the bud at E 11.5 and E 12.5 ( Fig. 3b and f) [42]. At later stages, Wnt7b is expressed in the ureter and distal collecting duct system ( Fig.…”
Section: Wnts In Renal Vesicle Formationmentioning
confidence: 94%
See 3 more Smart Citations
“…Wnt7b is weakly expressed in the Wolffian duct and the stalk of the UB but not in the vertical portion or tips of the bud at E 11.5 and E 12.5 ( Fig. 3b and f) [42]. At later stages, Wnt7b is expressed in the ureter and distal collecting duct system ( Fig.…”
Section: Wnts In Renal Vesicle Formationmentioning
confidence: 94%
“…Both Wnt6 and 9b are expressed throughout the Wolffian ducts and the ureteric bud/ proximal collecting duct system from E 10.5 through birth, although expression levels are lower in the ampullary tips (Fig. 3c,g,k,o and [42,43]). Wnt7b is weakly expressed in the Wolffian duct and the stalk of the UB but not in the vertical portion or tips of the bud at E 11.5 and E 12.5 ( Fig.…”
Section: Wnts In Renal Vesicle Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent works, scholars identified that the Pax2 transactivation domain is phosphorylated by the c-Jun N-terminal kinase (JNK) [29]. Research proves that the JNK can regulate downstream of the WNT signaling pathway, which is essential for the development of female reproductive ducts [30]. Other MDA candidate genes, such as LHX1, which also encodes for a transcription factor, participate in the period of mullerian duct formation [31].…”
Section: Discussionmentioning
confidence: 99%